Dopamine receptor D2 deficiency reduces mouse pup ultrasonic vocalizations and maternal responsiveness. (15th April 2013) - Curry, T.; Egeto, P.; Wang, H.; Podnos, A.; Wasserman, D.; Yeomans, J.
<x xml:space="preserve">Abstract</x> Dopamine signalling facilitates motivated behaviours, and the D2 dopamine receptor (D2R) is important in mother–infant interactions. D2R antagonists disrupt maternal behaviour and, in isolated rat pups, reduce ultrasonic vocalizations (USVs) that promote maternal interaction. Here, we examined the effects of genetic D2R signalling deficiency on pup‐dam interaction with Drd2 knockout (D2R KO) mice. Using heterozygous (HET) cross littermates, the effect of pup genotype on isolation‐induced USVs was quantified. Independent of parental genotype, D2R‐deficient pups emitted fewer USVs than wild type (WT) littermates in a gene dose‐dependent manner. Using reciprocal D2R KO‐WT crosses, we examined how parental genotype affects pup USVs. Heterozygous pups from D2R KO dams produced fewer USVs than HET pups from WT dams. Also, exposure to USV‐emitting pups increased plasma prolactin levels in WT dams but not in D2R KO dams, and KO dams showed delayed pup retrieval and nest building. These findings indicate the importance of the interaction between pup and dam genotypes on behaviour and further support the role of D2R signalling in maternal care.